Symptomology following COVID-19 among adults in Alberta, Canada: an observational survey study - Colleen Norris; Chester Ho; Jeffrey Bakal; Xueyi Chen; Tara Whitten; Balraj Mann (BMJ Open)
Objective Fatigue, headache, problems sleeping and numerous other symptoms have been reported to be associated with long COVID. However, many of these symptoms coincide with symptoms reported by the general population, possibly exacerbated by restrictions/precautions experienced during the COVID-19 pandemic. This study examines the symptoms reported by individuals who tested positive for COVID-19 compared with those who tested negative.Design Observational study.Setting The study was conducted on adult residents in Alberta, Canada, from October 2021 to February 2023.Participants We evaluated self-reported symptoms in 7623 adults with positive COVID-19 tests and 1520 adults who tested negative, using surveys adapted from the internationally standardised International Severe Acute Respiratory and emerging Infection Consortium (ISARIC)-developed COVID-19 long-term follow-up tools. These individuals had an index COVID-19 test date between 1 March 2020 and 31 December 2022 and were over 28 days post-COVID-19 testing.Primary outcome measures The primary outcomes were to identify the symptoms associated with COVID-19 positivity and risk factors for reporting symptoms.Results Fatigue was the top reported symptom (42%) among COVID-19-positive respondents, while headache was the top reported symptom (32%) in respondents who tested negative. Compared with those who tested negative, COVID-19-positive individuals reported 1.5 times more symptoms and had higher odds of experiencing 31 out of the 40 listed symptoms during the postinfectious period. These symptoms included olfactory dysfunction, menstruation changes, cardiopulmonary and neurological symptoms. Female sex, middle age (41–55 years), Indigeneity, unemployment, hospital/intensive care unit (ICU) admission at the time of testing and pre-existing health conditions independently predicted a greater number and variety of symptoms.Conclusions Our results provide evidence that COVID-19 survivors continue to experience a significant number and variety of symptoms. These findings can help inform targeted strategies for the unequally affected population. It is important to offer appropriate management for symptom relief to those who have survived the acute COVID-19 illness.